2022
DOI: 10.1177/20406207221090150
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the BNT162b2 mRNA Covid-19 vaccine in patients with chronic lymphocytic leukemia: a prospective study

Abstract: Introduction: Immunization of patients with chronic lymphocytic leukemia (CLL) with vaccines against several infectious diseases has proven insufficient. Data on seroconversion of patients with CLL after vaccination against severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) are still young, but accumulating evidence shows low seroconversion rates. Methods: We conducted a prospective, noninterventional study evaluating the safety and immunogenicity of two doses of the BNT162b2 mRNA Covid-19 vaccine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In an in-press study from our group, we showed that patients with CLL have suboptimal response to the BNT162b2 vaccine [11]. In the present study, we assessed the immunogenicity of a third dose of the BNT162b2 COVID-19 vaccine in patients with CLL.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In an in-press study from our group, we showed that patients with CLL have suboptimal response to the BNT162b2 vaccine [11]. In the present study, we assessed the immunogenicity of a third dose of the BNT162b2 COVID-19 vaccine in patients with CLL.…”
Section: Introductionmentioning
confidence: 89%
“…This is an extension of a previous study on the immunogenicity and safety of two doses of the BNT162b2 mRNA COVID-19 vaccine in patients with CLL [11]. Adult patients with CLL from three tertiary hospitals in Athens, Greece, vaccinated against SARS-CoV-2 with three doses of the BNT162b2 mRNA COVID-19 vaccine participated in the present study after providing a written informed consent.…”
Section: Patientsmentioning
confidence: 96%
See 2 more Smart Citations
“…Circulating antibody levels were most closely correlated with treatment history. 9,37 After 2-dose vaccination, anti-spike (S) IgG was detected in 6/15 (40%) patients, including 2/6 (33%) off-therapy (#210, 212); 2/2 (100%) treatment-naïve (#211, 213); 1/4 (25%) on active venetoclax (#203); 0/3 (0%) on ibrutinib; 1/4 (25%) on anti-CD20 of less than 12 months (#209) (Figures. 2A and 3A; Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%